2020
DOI: 10.1186/s12960-020-00506-7
|View full text |Cite
|
Sign up to set email alerts
|

A health care professionals training needs assessment for oncology in Uganda

Abstract: Background Cancer incidence and mortality in sub-Saharan Africa are increasing and do account for significant premature death. The expertise of health care providers is critical to downstaging cancer at diagnosis and improving survival in low- and middle-income countries. We set out to determine the training needs of health care providers for a comprehensive oncology services package in selected hospitals in Uganda, in order to inform capacity development intervention to improve cancer outcomes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…This similarity reflects the increased demand for total quality management within medical laboratories across Africa [ 21 23 ]. Contrary to the findings of the present study, healthcare professionals in Uganda cited research and audit as the domain with the largest training need [ 24 ] while health workers in the United Kingdom preferred topics that addressed anxiety and lack of confidence [ 25 ]. The training needs of health workers may vary by location.…”
Section: Discussioncontrasting
confidence: 90%
“…This similarity reflects the increased demand for total quality management within medical laboratories across Africa [ 21 23 ]. Contrary to the findings of the present study, healthcare professionals in Uganda cited research and audit as the domain with the largest training need [ 24 ] while health workers in the United Kingdom preferred topics that addressed anxiety and lack of confidence [ 25 ]. The training needs of health workers may vary by location.…”
Section: Discussioncontrasting
confidence: 90%
“…Gaspard & Yang in their study identified that continuous Professional Education (CPE) had the highest average difference score, closely followed by research/audit activities, management/supervisory skills, clinical tasks, communication and teamwork, and administration (12). Similarly in a study conducted by Byamugisha et al among health care professional in Uganda "research and audit" domain was identified as the priority area for training interventions to improve oncology services (17). A study conducted in a Tertiary hospital in China concluded that nurses' scientific research participation and self-rated research ability were below the optimal despite that they had relatively high research-training needs.…”
Section: Discussionmentioning
confidence: 94%